2013
DOI: 10.1002/lt.23598
|View full text |Cite
|
Sign up to set email alerts
|

In utero transplanted human hepatocytes allow postnatal engraftment of human hepatocytes in pigs

Abstract: In utero cell transplantation (IUCT) can lead to postnatal engraftment of human cells in the xenogeneic recipient. Most reports of IUCTs have involved hematopoietic stem cells. It is unknown if human hepatocytes used for IUCT in fetal pigs will lead to engraftment of these same cells in the postnatal environment. In this study, fetal pigs received direct liver injections of 1×107 human hepatocytes in utero and were delivered by cesarean-section at term. Piglets received a second direct liver injection of 5×107… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…[50] As liver injury can be initiated by stopping NTBC at any time in development, FAH −/− pigs could be used to test efficacy of gene therapy and in utero cell transplant approaches at any point during gestation, providing a unique disease model that is currently unavailable. Additionally, FAH-deficiency during development may provide a strong selective advantage for the expansion of transplanted human hepatocytes in utero,[51] potentially allowing rapid repopulation of the FAH −/− liver with cells[42] that could be used for various cell therapy approaches for myriad liver disorders. A comparable strategy has already been demonstrated in the pig for generating exogenic pancreas in an apancreatic pig by way of blastocyst complementation.…”
Section: Section 4: Discussionmentioning
confidence: 99%
“…[50] As liver injury can be initiated by stopping NTBC at any time in development, FAH −/− pigs could be used to test efficacy of gene therapy and in utero cell transplant approaches at any point during gestation, providing a unique disease model that is currently unavailable. Additionally, FAH-deficiency during development may provide a strong selective advantage for the expansion of transplanted human hepatocytes in utero,[51] potentially allowing rapid repopulation of the FAH −/− liver with cells[42] that could be used for various cell therapy approaches for myriad liver disorders. A comparable strategy has already been demonstrated in the pig for generating exogenic pancreas in an apancreatic pig by way of blastocyst complementation.…”
Section: Section 4: Discussionmentioning
confidence: 99%
“…12 Fisher et al injected human hepatocytes directly into the fetal pig liver on gestational day 40 and again 1 week after birth, resulting in successful engraftment of human hepatocyte in postnatal pigs. 13 Although this concept enables effective development of organs, it is inevitable that some xenogeneic components remain in the engineered organs. Furthermore, the maintenance of transplanted human cells in a pig scaffold is also important.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…The recent achievements in both rodent and pig models are summarized in Table 1. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] One of the approaches is to utilize the organogenetic potential of scaffold animals. Although it is still hard to control complex of signals and interactions for organ development, this concept allows cells to make use of almost optimal environment.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…A number of studies have shown hepatocyte engraftment and function across a species barrier, but while the exclusion of vascular structures may address some of the immunological issues associated with xenotransplantation, the possibility of xenozoonosis remains (14). Another viable option in the future may be the use of fumarylacetoacetate hydrolase (FAH) deficient pigs as incubators for in vivo expansion of human hepatocytes, as in utero cell transplantation can lead to postnatal engraftment of functional human cells in the xenogeneic recipient, possibly allowing for large-scale expansion of human hepatocytes in genetically-engineered pigs (15). Stem cells are also a potential source of hepatocyte-like cells (HLCs), and will be discussed in the following section.…”
Section: Primary Hepatocytesmentioning
confidence: 99%